Pekerja Anak Sektor Informal di Indonesia: Situasi Terkini dan Tantangan ke Depan (Analisis Data Susenas 2019) - Dodi Satriawan (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2021)
Children are very valuable assets in the future, especially as human resources that will continue development. Children have the right to get opportunities to develop, grow healthy and have proper education. However, until now there are still many children who have not perfectly obtained these rights because they have to work. The involvement of children in the labor market is one of the problems in the field of employment, especially by looking at the condition of the majority of child laborers in the informal sector. The 2017 Susenas results until 2019 show that the percentage of child laborers working in the informal sector is always above 70 percent. Characteristics of child labor in the informal sector are characterized by the highest level of education at the elementary level and have not finished elementary school. More than 50 percent of informal child workers are still actively attending school at the formal education level. The informal sector child laborers in urban areas mostly work in the service sector while in rural areas there are in the agricultural sector. More than 50 percent of informal sector child laborers are household members with household expenses in the lowest 40 percent group.